Analysis of thermomechanical self-oscillation In Perpendicular Free Cutting - G.K, Korendyasev (International Journal of Engineering and Technology, 2018)
The results of the finite element modeling and analysis of thermomechanical phenomena arising from the of cutter self-excitation in perpendicular free cutting of metals are given. It is shown that the cause of self-excitation of self-oscillations is the nonlinear temperature dependence of the blankâ€™s mechanical characteristics. Modeling detected the effects of self-excitation and the establishment of self-oscillations, revealed the conditions for the propensity to the occurrence of self-oscillations for various materials.Â Â